Effect Of Slaughtering Methods On Meat Quality Indicators, Chemical Changes And Microbiological Quality Of Broiler Chicken Meat During Refrigerated Storage - Ahmed Hafiz O; Zaiton Hassan; Mohd Nazmi Abd Manap (The International Organization of Scientific Research, 2024)
Slaughtering is a process of bringing an animal to a quick painless death. It involves throat cutting for maximum blood drainage and the amount of blood retained is dependent on the method of slaughter. This study investigated the effect of slaughtering method (Halal and Chinese methods) on meat quality indicators and shelf life of broiler chicken breast meat. Quality indicators such as pH, drip loss and colour (L*, a*, b*) were significantly (P˂0.05) higher for birds slaughtered with the Chinese method (pH= 6.17, L*= 56.42, a*= 8.36, b*= 19.2, drip loss= 0.58) than the halal method. There were no differences in cook loss, thaw loss and toughness obtained from both slaughtering methods. Iron (Fe) content for birds slaughtered using Chinese method was 13.77 mg/kg which was significantly higher than those slaughtered using the halal method (10.00 mg/kg). The haem iron content were 2.55 and 3.25 mg/100g sample respectively for birds slaughtered using both halal and Chinese methods and this decreased during storage at 40C for 9 days. Higher microbial count after 9 days of refrigerated storage (6.28 cfu/g) were recorded for birds slaughtered using Chinese method as compared with the halal method (5.05 cfu/g). Results from this study indicate that method of slaughter for poultry significantly affects the quality and shelf life of meat produced. Keywords -broiler chicken, quality indicators, chemical changes, microbiological quality, slaughtering methods.